The Sleep Patterns of Children and Adolescents with Chronic Conditions and Their Families: An Integrative Literature Review - Xavier, Welker da Silva; Abreu, Madalena Paulos; Nunes, Michelle Darezzo Rodrigues; Silva-Rodrigues, Fernanda Machado; da Silva, Liliane Faria; de Araújo, Barbara Bertolossi Marta; De Bortoli, Paula Saud; Neris, Rhyquelle Rhibna; Nascimento, Lucila Castanheira (Children (Basel), 2024)
Sleep is of vital necessity for health, and it has a restorative and protective function for children and adolescents with chronic conditions and their families. The purpose of this study was to identify the scientific production on sleep patterns in children and adolescents with chronic conditions and their families. This integrative review was conducted between March and June 2022 using the databases of MEDLINE, Web of Science, CINAHL and PsycINFO. The articles included were original papers published between January 2007 and mid-2022. Excluded were review studies that did not evaluate sleep and whose participants did not have chronic conditions or were not children, adolescents and/or their families. The searches returned 814 abstracts. After exclusions, 47 studies were selected to be read in full; of these, 29 were selected and were grouped empirically into four categories: major alterations in the sleep patterns of children and adolescents with chronic conditions; the relationship between sleep disorders and symptoms in children and adolescents with chronic conditions; the impaired sleep patterns of families of children and adolescents with chronic conditions; and sleep alterations and their relationship with other problems in families of children and adolescents with chronic conditions. All studies showed sleep pattern impairment in children and adolescents with chronic conditions as well as their families.